Comparison of consumer knowledge about Campylobacter, Salmonella and Toxoplasma and their transmissibility via meat: results of a consumer study in Germany - K. A. Henke; T. Alter; M. G. Doherr; R. Merle (BMC, 2020)
Abstract Background Campylobacter is the most commonly reported causative agent of foodborne bacterial infection in Germany, and contaminated chicken meat is an important source of this zoonotic agent. The aim of this study was to determine the knowledge of consumers in Germany about Campylobacter, Salmonella and Toxoplasma and their transmissibility via meat. In addition, we investigated the level of knowledge between selected consumer groups and whether the results coincided with those of international studies. Methods We conducted a cross-sectional survey of 1008 consumers in Germany via an online panel to record, analyse and evaluate the state of knowledge about Campylobacter, Salmonella and Toxoplasma. The participants were selected according to age, gender and federal states to be representative of the German population. Results Overall, 68.3% of the respondents had never heard of Campylobacter, 20.2% had heard of Campylobacter but did not know how to protect themselves, and only 11.5% knew how to protect themselves from Campylobacter infections. Slightly more than half (52.2%) of the respondents who had at least heard of Campylobacter knew that Campylobacter was transmissible via meat. Knowledge increased significantly with age. Participants over 60 years old knew about Campylobacter almost three times as often as the 16- to 19-year-old comparison group (OR = 2.982). Consumers who had at least a secondary school certificate were almost twice as likely to know about Campylobacter as those who had no school certificate or a lower secondary school certificate (OR = 1.899). Participants who were not actors in the food chain were significantly less frequently informed about Campylobacter than were those who were actors in the food chain. Consumer knowledge of Toxoplasma was better than that of Campylobacter. Consumers have the most knowledge about Salmonella. Conclusions Consumers in Germany are predominantly poorly informed about Campylobacter and the transmission route via meat. General knowledge of Toxoplasma is better than that of Campylobacter. Among the three pathogens, consumers are best informed about Salmonella. This finding highlights the importance of making existing information materials more accessible to consumers in the future to increase their knowledge, with the objective of reducing the incidence of Campylobacter infections.